Indicator circuit with incremental clustering to measure operators' efficiency in telecommunications industry - Komsan Suriya (2018)
© Serials Publications Pvt. Ltd. The indicator circuit with incremental clustering (ICIC) can aggregate many indicators into a composite index using the process of incremental clustering in the score assignment. This study applies the ICIC to compose the scores of firms' efficiency from 6 indicators of 1, 000 top firms in Thailand in 2003. Then it selects 17 firms in the telecommunications industry to measurethe performance of ICIC and compares to that of the indicator circuits with reference points (ICRP) introduced by Suriya(2015). The results reveal that the ICIC solves many problems occurred in ICRP. First, it differentiates the efficiency of the firms better. Second, it ranks the firms in a more reasonable way. Third, it is more flexible to adjust the range of the scores by the incremental distances from the highest score.